PREFERENSI REMAJA TERHADAP KONTEN MEDIA SOSIAL YOUTUBE - Syafei Sikumbang (Marcommers : Jurnal Marketing Communication and Advertising, 2026)
Preferency teenegeers on social media yuotube is interesting and important to be discussed. Therefore, the purpose of this research is trying to understand how teenegeers consume social media, since social media especially social media youtube is one of the media that is interested by many people and teenegeers. In this research is decided media content category entertainment for teenegeers such as film, sport and music. Method that is used study Qualitative paradigm and survey analize. The aim of survey method is to give freedom to the responden to respond the question according to their perception. For obtaining sampel in this research, researcher uses Yamane formula and as sample are student Mecubuana Univercity. The conclusion of this reserarh is that most of teenegeers are consuming adventured film, badminton sport and Pop music. As attitude of teenegers that they know exatcly what they see and most of them are like.